Rare cause of jaundice in a post liver transplant patient. Issue 4 (16th July 2015) - She, W.H.; Chok, K.S.H.; Lo, R.C.L.; Chan, S.C.; Lo, C.M.
Abstract A hepatitis B virus carrier suffering from acute flare of chronic hepatitis B infection underwent deceased‐donor liver transplantation. He was put on the immunosuppressive agent tacrolimus. On routine follow‐up, he was found to have abnormal liver function. Computed tomography scan of the abdomen did not show any dilatation of the biliary system. Liver biopsy showed scattered microabscesses, and a microgranuloma was detected. Endoscopic retrograde cholangiography was performed and a biliary anastomotic stricture (BAS) was noted. In addition, the Chinese liver fluke, Clonorchis sinensis, was discovered. Balloon dilatation and stenting were performed. The patient was given a course of praziquantel. His liver function improved and normalized. We present the case of a liver transplant recipient with cholangitis caused by C. sinensis infestation and infection and biliary obstruction resulting from BAS.